Implementation of Fostering an Attitude of Tolerance in Merdeka Curriculum on the Science Learning Process - Hasan Mahfud; Sri Marmoah; Jenny I.S. Poerwanti; Sukarno; Supianto; Siti Istiyati (Jurnal Penelitian Pendidikan IPA, 2024)
The image of tolerance at SDN Pajang Surakarta is demonstrated through the existence of harmony in the school environment, despite differences in ethnicity, religion, and ability. The entire school community demonstrates mutual respect and tolerance so that peace can be created. The objectives of this study are to describe the implementation of measures to promote tolerant attitudes in students, and to promote tolerant attitudes in students through learning activities at school. This study uses a qualitative research methodology, collecting data through observations, interviews, and document analysis.  Results of this study indicate that the implementation of promoting social attitudes is done through integrating the concept of tolerance, the value of tolerance in the learning process, and through extracurricular activities as well as through projects to strengthen the profile of Pancasila Students (P5). The school's socially tolerant attitude promotes peace in the school environment and an attitude of mutual respect and awareness. The researcher concluded that the implementation of fostering an attitude of tolerance in the Merdeka curriculum on the learning process has been carried out well through integrated learning, extra-curricular activities carried out outside of class time, and Pancasila student strengthening project activities (P5).